Feminist interpretation: Feminist perspectives on reproductive health in the Qur'an - Fauji, Hari; Ghoni, Abdul (UIN Sunan Gunung Djati Bandung, 2025)
Emphasizing the importance of reproductive health, especially for women, because reproductive health is a guarantee of their survival. The research is a qualitative and descriptive analysis using primary sources Q.S Maryam 22-26, Qs. al-Baqarah: 233, as well as secondary sources taken from tafsir books and other scientific works on the term al-Makhad and yurdi’na, which are reproductive organs. The results of the discussion showed that women cannot be free from the feeling of contractions during childbirth. This is also explained in the Qur'an when telling about the process of Jesus' birth that Maryam went through in (QS. Maryam: 22-26). Pronunciation of al-Makhad in this verse, it is better known as pain during childbirth or commonly known in contemporary terms, namely contractions. A woman's pain during childbirth should not be aggravated by adverse environmental conditions. Women who give birth must have the support of those closest to them, especially her husband, to reduce the burden of the pain she is experiencing. Then breastfeeding normally uses the term yurdi’na, in fact breast milk is a form of sustenance that fathers must give to their children through the mother through the act of yurdi’na (breastfeeding). This research is expected to contribute to new knowledge and not discriminate against women when experiencing the psychological burden of childbirth and breastfeeding, and is useful for Qur'anic researchers related to the discussion of women's reproductive health.